Living arrangements and food security of a sample of older Palestinian refugees in Lebanon - Nadine R. Sahyoun; Anniebelle Sassine; Anna Vaudin; Fayrouz Sakr-Ashour; Hala Ghattas (Journal of Global Health Reports)
# Background